# What is the derivative of #f(t) = (t^3-e^(3t-1) , 3t^2+2e^t ) #?

The derivative of the parametric function is

By signing up, you agree to our Terms of Service and Privacy Policy

The derivative of ( f(t) = (t^3 - e^{3t - 1}, 3t^2 + 2e^t) ) with respect to ( t ) is ( f'(t) = (3t^2 - 3e^{3t - 1}, 6t + 2e^t) ).

By signing up, you agree to our Terms of Service and Privacy Policy

- Consider the parametric equations x = 3t - 5 and y = 2t + 3 how do you eliminate the parameter to find a Cartesian equation of the curve?
- What is the derivative of #f(t) = (tcos^2t , t^2-cost ) #?
- How do you differentiate the following parametric equation: # x(t)=t-5, y(t)= t^2#?
- How do you differentiate the following parametric equation: # x(t)=t^2-t, y(t)=e^t+cost #?
- How do you find the parametric equations of line that passes through the points (1, 3, 2) and ( -4, 3, 0)?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7